Nonmotor Symptoms Groups in Parkinson's Disease Patients: Results of a Pilot, Exploratory Study. (4th May 2011) - Perez Lloret, Santiago; Rossi, Malco; Merello, Marcelo; Rascol, Olivier; Cardinali, Daniel P.
Abstract : Nonmotor symptoms (NMS) like neuropsychiatric symptoms, sleep disturbances or autonomic symptoms are a common feature of Parkinson's disease (PD). To explore the existence of groups of NMS and to relate them to PD characteristics, 71 idiopathic non-demented PD out-patients were recruited. Sleep was evaluated by the PD Sleep Scale (PDSS). Several neuropsychiatric, gastrointestinal and urogenital symptoms were obtained from the NMSQuest. Sialorrhea or dysphagia severity was obtained from the Unified PD Rating Scale activities of daily living section. MADRS depression scale was also administered. Exploratory factor analysis revealed the presence of 5 factors, explaining 70% of variance. The first factor included PDSS measurement of sleep quality, nocturnal restlessness, off-related problems and daytime somnolence; the second factor included nocturia (PDSS) and nocturnal activity; the third one included gastrointestinal and genitourinary symptoms; the forth one included nocturnal psychosis (PDSS), sialorrhea and dysphagia (UPDRS); and the last one included the MADRS score as well as neuropsychiatric symptoms. Sleep disorders correlated with presence of wearing-off, nocturia with age >69 years, and nocturnal psychosis with levodopa equivalent dose or UPDRS II score. Neuropsychiatric symptoms correlated with UPDRS II+III score and non-tricyclic antidepressants. These results support the occurrence of significant NMS grouping in PD patients.